Deconstructing Religiosity-Green Finance Relationship: The Role of Organizational Factors - Girindratama, Muhammad Wisnu; Maulidi, Ach; Alnajar, Ali Elazumi Ali; Mela, Ali Abdullah (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research originality: This study links religiosity to green finance in emerging-market banks, highlighting internal drivers, green HRM, organizational identity, and leadership over external pressures. It uniquely shows how personal beliefs shape sustainable finance through cultural and theoretical pathways. Research objectives: The research aims to examine how religiosity affects the willingness of banks to engage in green finance, and under what conditions this relationship is strengthened. Research methods: The research employs a quantitative survey method involving employees across both private and state-owned banking institutions within the specified province, involving a cross-section of 43 banks. Structural equation modelling is used to test the hypothesised relationships. Empirical result: The results reveal that religiosity influences green finance indirectly through the enhancement of internal organisational capacities. Specifically, religiosity strengthens environmental values and practices within human resource systems, leadership approaches, and organisational identity, which in turn foster commitment to green financial strategies. Implications: These findings highlight the strategic importance of cultural and leadership-based resources in promoting environmental sustainability in the banking sector. JEL Classification: G21, Q56, M14, J53, L21